2009
DOI: 10.1016/j.bandc.2009.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Brain oscillations during semantic evaluation of speech

Abstract: Changes in oscillatory brain activity have been related to perceptual and cognitive processes such as selective attention and memory matching. Here we examined brain oscillations, measured with electroencephalography (EEG), during a semantic speech processing task that required both lexically mediated memory matching and selective attention. Participants listened to nouns spoken in male and female voices, and detected an animate target (p = 20%) in a train of inanimate standards or vice versa. For a control ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 52 publications
(86 reference statements)
8
94
0
Order By: Relevance
“…Hertrich et al (2015) examined spectrotemporal characteristics of the MEG signal time-locked to the onset of presupposition triggers and found a suppression of spectral power within the alpha band (from 6 to 16 Hz) for infelicitous (4.a) vs. felicitous (4.b) sentences across two time-windows: 0 -500 ms and 2000 ms -2500 ms. The reduction of alpha activity is generally associated with increased mental load and cognitive effort (Bastiaansen & Hagoort, 2006; Klimesch, 1996;Shahin, Picton, & Miller, 2009).Although the timing of presupposition processing did not closely mirror the timing 7 reported by Kirsten et al (2014), the authors provided a similar explanation of the biphasic pattern that they observed. In particular, the initial suppression of alpha power (0 -500 ms) was taken to reflect violations of lexical expectancy, and the later one (2000 -2500 ms) was linked with attempts to reinterpret presupposition triggers within the given context.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Hertrich et al (2015) examined spectrotemporal characteristics of the MEG signal time-locked to the onset of presupposition triggers and found a suppression of spectral power within the alpha band (from 6 to 16 Hz) for infelicitous (4.a) vs. felicitous (4.b) sentences across two time-windows: 0 -500 ms and 2000 ms -2500 ms. The reduction of alpha activity is generally associated with increased mental load and cognitive effort (Bastiaansen & Hagoort, 2006; Klimesch, 1996;Shahin, Picton, & Miller, 2009).Although the timing of presupposition processing did not closely mirror the timing 7 reported by Kirsten et al (2014), the authors provided a similar explanation of the biphasic pattern that they observed. In particular, the initial suppression of alpha power (0 -500 ms) was taken to reflect violations of lexical expectancy, and the later one (2000 -2500 ms) was linked with attempts to reinterpret presupposition triggers within the given context.…”
mentioning
confidence: 79%
“…Hertrich et al (2015) examined spectrotemporal characteristics of the MEG signal time-locked to the onset of presupposition triggers and found a suppression of spectral power within the alpha band (from 6 to 16 Hz) for infelicitous (4.a) vs. felicitous (4.b) sentences across two time-windows: 0 -500 ms and 2000 ms -2500 ms. The reduction of alpha activity is generally associated with increased mental load and cognitive effort (Bastiaansen & Hagoort, 2006; Klimesch, 1996;Shahin, Picton, & Miller, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of alpha suppression that arises after participants listened to severely degraded speech could reflect neural oscillators that keep alpha power high to rule out erroneous activations in relevant language-and meaning-related areas (Obleser & Weisz, 2012) and is mostly observed after a full linguistic utterance (Klimesch et al, 2007;Shahin, Picton, & Miller, 2009). Another recent study demonstrated a parametric suppression in alpha band activity as items increasingly matched real words, with lowered functional inhibition for more word-like input (Strauß, Kotz, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining EEG oscillatory activity, which has been implicated in the processing of complex auditory features Hannemann et al 2007;Morillon et al 2012;Shahin et al 2009b), showed that an increase in beta (14 -30 Hz) and gamma (Ͼ30 Hz) oscillatory activity reflected binding of AV percepts (Keil et al 2011;Senkowski et al 2007). In Keil et al (2011), beta activity was localized to distributed brain regions, including the superior temporal cortex (STC).…”
mentioning
confidence: 99%